(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The paper presents the results of a survey on the scale insect fauna carried out over different years in the Alpine Aosta Valley (Italy). A total of 54 species have been collected in this Italian region. Of these, 7 are new for the Italian fauna: Neomargarodes festucae Archangelskaja, Chaetococcus sulci (Green), Peliococcus marrubii (Kiritshenko), Rhodania porifera Goux, Eriococcus placidus Green, Rhizopulvinaria saxatilis Canard and R. spinifera Borchsenius. Two other species previously recorded from the Aosta Valley as Rhizoecus caesii Schmutterer and Mirococcopsis nagyi Kozar proved their pertinence respectively to Rhizoecus pratensis Borchsenius & Tereznikova and Volvicoccus volvifer Goux. The opportunity is taken to synonyrnize Antoninella inaudita Kiritshenko, 1938, n. syn. with Antoninella parkeri (Balachowsky, 1936) n. comb. The peculiar climate of the Aosta Valley allows the establishment of several thermophilous or xerophilous species, some of which are considered rare species, such as Neomargarodes festucae, Antoninella parkeri, Chaetococcus sulci, Rhizoecus albidus Goux, Rhodania porifera, Peliococcus marrubii, Volvicoccus volvifer, Cerococcus cycliger Goux, Rhizopulvinaria artemisiae (Signoret), R. spinifera, Quadraspidiotus labiatarum (Marchal).